2023
DOI: 10.3390/horticulturae9111184
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biostimulants on Fruit Quality of Processing Tomato Grown under Deficit Irrigation

Vasiliki Liava,
Christina Chaski,
Mikel Añibarro-Ortega
et al.

Abstract: Water shortage can be a restrictive factor for the growth and quality of vegetable crops. Considering the alleviating effects of biostimulant application against water stress, this study aimed to investigate the effect of four biostimulant products (protein and amino acids with carboxylic acids (Tr1); protein and amino acids with seaweed extracts (Tr2); humic and fulvic acids with seaweed extracts (Tr3); SiO2 (Tr4); and control (no biostimulants added)) and two irrigation systems (regulated deficit irrigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…In general, the application of both doses of Green Leaves produced a significant increase in the concentration of soluble sugars in the plants compared with control plants (Figure 2a), which is related to the higher photosynthetic activity (Table 4) and the enhanced production of biomass and leaf area (Table 1). Other studies in rice and tomato plants also suggest that biostimulant application enhanced photosynthesis performance, which in turn increased soluble sugar accumulation [37,38].…”
Section: Photosynthesis-related Parametersmentioning
confidence: 87%
See 1 more Smart Citation
“…In general, the application of both doses of Green Leaves produced a significant increase in the concentration of soluble sugars in the plants compared with control plants (Figure 2a), which is related to the higher photosynthetic activity (Table 4) and the enhanced production of biomass and leaf area (Table 1). Other studies in rice and tomato plants also suggest that biostimulant application enhanced photosynthesis performance, which in turn increased soluble sugar accumulation [37,38].…”
Section: Photosynthesis-related Parametersmentioning
confidence: 87%
“…and the enhanced production of biomass and leaf area (Table 1). Other studies in rice and tomato plants also suggest that biostimulant application enhanced photosynthesis performance, which in turn increased soluble sugar accumulation [37,38].…”
Section: Photosynthesis-related Parametersmentioning
confidence: 87%
“…In this regard, it is highlighted that the effects of different biostimulants on tomato quality obtained in the literature are very different from each other. These differences could be due to several factors, among which are the biostimulant composition [ 35 ] and the technique of their application (when and how to apply) [ 73 , 74 ], the tomato genotype used [ 17 , 70 ] and the climatic conditions, such as temperature [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly due to the variety of underlying factors in crop fields, including weather variability, climate fluctuations, soil type, and field management [ 14 ]. Furthermore, the application of biostimulants has recently been extensively studied on tomato crops under abiotic stress conditions (temperature, drought, salinity, nutrition) to enhances growth, improve yield and quality, and minimize the negative effects of stress [ 23 , 33 , 34 , 35 , 36 , 37 , 38 ]. Several studies have also been conducted under mineral nutritional conditions [ 17 , 39 , 40 ], but comparative research on fields of different levels of fertility is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, biostimulants are novel substances that have recently been used for enhancing the phytoremediation efficiency of contaminated soils [19]. It has been recognized that utilizing biostimulants in crop production increases plant vigor, crop yield, and resistance to biotic and abiotic stressors [16,[20][21][22]. Recent studies have confirmed that these products can reduce the bioavailability of PTEs in soil and their toxic effects to plants [23][24][25].…”
Section: Introductionmentioning
confidence: 99%